2021
DOI: 10.3390/medicina57101071
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Enamel Matrix Derivative on Periodontal Regeneration under Diabetic Conditions

Abstract: Background and Objectives: Enamel matrix derivative (EMD) is a biomaterial used for periodontal regenerative therapy due to its properties of stimulating cementum development and bone synthesis. Diabetes is a chronic condition that affects healing and predisposes to infection. The aim of this review was to evaluate the current studies available on the application and results of EMD for periodontal regenerative therapy under diabetic conditions. Materials and Methods: Five databases (PubMed, ResearchGate, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…4,5 Previous studies have demonstrated the clinical and experimental efficacy of enamel matrix derivatives (EMDs) in promoting periodontal regeneration. [6][7][8][9][10][11] EMDs are hierarchical complexes of proteins, with amelogenin being the main component found in enamel matrix, secreted by ameloblasts. Our previous research has focused on the development of recombinant human amelogenin (rhAm) and its ability to enhance the proliferation, osteogenic differentiation, and migration of human periodontal ligament cells (hP-DLCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Previous studies have demonstrated the clinical and experimental efficacy of enamel matrix derivatives (EMDs) in promoting periodontal regeneration. [6][7][8][9][10][11] EMDs are hierarchical complexes of proteins, with amelogenin being the main component found in enamel matrix, secreted by ameloblasts. Our previous research has focused on the development of recombinant human amelogenin (rhAm) and its ability to enhance the proliferation, osteogenic differentiation, and migration of human periodontal ligament cells (hP-DLCs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the clinical and experimental efficacy of enamel matrix derivatives (EMDs) in promoting periodontal regeneration 6–11 . EMDs are hierarchical complexes of proteins, with amelogenin being the main component found in enamel matrix, secreted by ameloblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lack of nutrition in people suffering from IBD and the occurrence of autoimmune inflammatory processes at the site of bone and implant junction, along with other processes in various parts of the organism, may lead to insufficient osseous formation around the implant [ 6 , 7 ]. The risk of failure and the poor implant prognosis of patients with IBD is commonly acknowledged by medical specialists, knowing that other systemic disorders also have the capacity to induce the same undesirable consequences [ 7 , 8 , 9 ]. Another aspect that should be taken into account is the peri-implant bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 By applying regenerative therapeutic approaches, cementum can be restored by stimulation of cementogenesis, 10,11 even though, current therapeutic strategies are limited and outcomes unpredictable. 4,12,13 During formation of cellular cementum, a portion of cementoblasts is embedded in the cementoid matrix and become cementocytes. A significant barrier to improved therapies for cementum regeneration is that the cementocyte remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the integrity of cellular cementum protects the tooth root from resorption and is fundamental in maintaining occlusal relationships and its function in tooth support 8,9 . By applying regenerative therapeutic approaches, cementum can be restored by stimulation of cementogenesis, 10,11 even though, current therapeutic strategies are limited and outcomes unpredictable 4,12,13 …”
Section: Introductionmentioning
confidence: 99%